plzzz ans.....PROVE THE FOLLOWING
Attachments:
![](https://hi-static.z-dn.net/files/db4/ee3b5efa33790436d2a6545ade3b0b01.jpg)
Answers
Answered by
3
HELLO DEAR,
![\frac{ \sin \alpha }{ \cot \alpha + \cosec \alpha } \\ \\ = \frac{ \sin \alpha }{ \frac{ \cos \alpha }{ \sin\alpha } + \frac{1}{ \sin \alpha } } \\ \\ = \frac{ \sin \alpha }{ \frac{ \cos \alpha + 1 }{ \sin\alpha } } \\ \\ = \frac{ {sin \alpha }^{2} }{(1 + \cos \alpha )} \\ \\ = \frac{(1 - {cos}^{2} \alpha )}{(1 + cos \alpha )} \\ \\ = \frac{(1 - cos \alpha )(1 + cos \alpha )}{(1 + cos \alpha )} \\ \\ = (1 - cos \alpha ) \frac{ \sin \alpha }{ \cot \alpha + \cosec \alpha } \\ \\ = \frac{ \sin \alpha }{ \frac{ \cos \alpha }{ \sin\alpha } + \frac{1}{ \sin \alpha } } \\ \\ = \frac{ \sin \alpha }{ \frac{ \cos \alpha + 1 }{ \sin\alpha } } \\ \\ = \frac{ {sin \alpha }^{2} }{(1 + \cos \alpha )} \\ \\ = \frac{(1 - {cos}^{2} \alpha )}{(1 + cos \alpha )} \\ \\ = \frac{(1 - cos \alpha )(1 + cos \alpha )}{(1 + cos \alpha )} \\ \\ = (1 - cos \alpha )](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Csin+%5Calpha+%7D%7B+%5Ccot+%5Calpha+%2B+%5Ccosec+%5Calpha+%7D+%5C%5C+%5C%5C+%3D+%5Cfrac%7B+%5Csin+%5Calpha+%7D%7B+%5Cfrac%7B+%5Ccos+%5Calpha+%7D%7B+%5Csin%5Calpha+%7D+%2B+%5Cfrac%7B1%7D%7B+%5Csin+%5Calpha+%7D+%7D+%5C%5C+%5C%5C+%3D+%5Cfrac%7B+%5Csin+%5Calpha+%7D%7B+%5Cfrac%7B+%5Ccos+%5Calpha+%2B+1+%7D%7B+%5Csin%5Calpha+%7D+%7D+%5C%5C+%5C%5C+%3D+%5Cfrac%7B+%7Bsin+%5Calpha+%7D%5E%7B2%7D+%7D%7B%281+%2B+%5Ccos+%5Calpha+%29%7D+%5C%5C+%5C%5C+%3D+%5Cfrac%7B%281+-+%7Bcos%7D%5E%7B2%7D+%5Calpha+%29%7D%7B%281+%2B+cos+%5Calpha+%29%7D+%5C%5C+%5C%5C+%3D+%5Cfrac%7B%281+-+cos+%5Calpha+%29%281+%2B+cos+%5Calpha+%29%7D%7B%281+%2B+cos+%5Calpha+%29%7D+%5C%5C+%5C%5C+%3D+%281+-+cos+%5Calpha+%29)
---------L.H.S.---------
![2 + \frac{sin \alpha }{ \frac{cos \alpha }{sin \alpha } - \frac{1}{sin \alpha } } \\ \\ = 2 + \frac{sin \alpha }{ \frac{( - 1 + cos \alpha )}{sin \alpha } } \\ \\ = 2 + \frac{ {sin}^{2} \alpha }{( - 1 + cos \alpha )} \\ \\ = 2 + \frac{( 1 - cos \alpha )(1 + cos \alpha )}{ - (1 - cos \alpha )} \\ \\ = \frac{ - 2 + 1 + cos \alpha }{ - 1} \\ \\ = \frac{cos \alpha - 1}{ - 1} \\ \\ = \frac{ - (1 - cos \alpha )}{ - 1} \\ \\ =(1 - cos \alpha ) 2 + \frac{sin \alpha }{ \frac{cos \alpha }{sin \alpha } - \frac{1}{sin \alpha } } \\ \\ = 2 + \frac{sin \alpha }{ \frac{( - 1 + cos \alpha )}{sin \alpha } } \\ \\ = 2 + \frac{ {sin}^{2} \alpha }{( - 1 + cos \alpha )} \\ \\ = 2 + \frac{( 1 - cos \alpha )(1 + cos \alpha )}{ - (1 - cos \alpha )} \\ \\ = \frac{ - 2 + 1 + cos \alpha }{ - 1} \\ \\ = \frac{cos \alpha - 1}{ - 1} \\ \\ = \frac{ - (1 - cos \alpha )}{ - 1} \\ \\ =(1 - cos \alpha )](https://tex.z-dn.net/?f=2+%2B+%5Cfrac%7Bsin+%5Calpha+%7D%7B+%5Cfrac%7Bcos+%5Calpha+%7D%7Bsin+%5Calpha+%7D+-+%5Cfrac%7B1%7D%7Bsin+%5Calpha+%7D+%7D+%5C%5C+%5C%5C+%3D+2+%2B+%5Cfrac%7Bsin+%5Calpha+%7D%7B+%5Cfrac%7B%28+-+1+%2B+cos+%5Calpha+%29%7D%7Bsin+%5Calpha+%7D+%7D+%5C%5C+%5C%5C+%3D+2+%2B+%5Cfrac%7B+%7Bsin%7D%5E%7B2%7D+%5Calpha+%7D%7B%28+-+1+%2B+cos+%5Calpha+%29%7D+%5C%5C+%5C%5C+%3D+2+%2B+%5Cfrac%7B%28+1+-+cos+%5Calpha+%29%281+%2B+cos+%5Calpha+%29%7D%7B+-+%281+-+cos+%5Calpha+%29%7D+%5C%5C+%5C%5C+%3D+%5Cfrac%7B+-+2+%2B+1+%2B+cos+%5Calpha+%7D%7B+-+1%7D+%5C%5C+%5C%5C+%3D+%5Cfrac%7Bcos+%5Calpha+-+1%7D%7B+-+1%7D+%5C%5C+%5C%5C+%3D+%5Cfrac%7B+-+%281+-+cos+%5Calpha+%29%7D%7B+-+1%7D+%5C%5C+%5C%5C+%3D%281+-+cos+%5Calpha+%29+)
-----------R.H.S.---------------
I HOPE ITS HELP YOU DEAR,
THANKS
---------L.H.S.---------
-----------R.H.S.---------------
I HOPE ITS HELP YOU DEAR,
THANKS
rohitkumargupta:
tumne bhi acha kiya hai
Answered by
1
Heya!!!
Here is your answer,
Hope it helps you,
Thank you.
Here is your answer,
Hope it helps you,
Thank you.
Attachments:
![](https://hi-static.z-dn.net/files/d7b/e857cb1498696bcb5e5ec74ce68bccb4.jpg)
Similar questions